Corporate Governance, ESG Disclosure, and Firm Value: Evidence from Public Companies in Indonesia - Sari, Dian Permata; Fikri, Muhammad; Kartika, Rina; Tanwattana, Nattapat (Journal of Economics and Management, 2025)
This study examines the influence of corporate governance and Environmental, Social, and Governance (ESG) disclosure on firm value in publicly listed companies in Indonesia. The research utilizes a quantitative approach with secondary data derived from annual and sustainability reports of 120 non-financial companies listed on the Indonesia Stock Exchange (IDX) between 2018 and 2022. Corporate governance is measured using board characteristics, including board size, independence, and gender diversity, while ESG disclosure is assessed through a modified GRI-based content analysis index. Firm value is proxied by Tobin’s Q. The results of panel data regression analysis indicate that board independence and ESG disclosure have a significant positive impact on firm value, while board size shows a negative but insignificant effect. These findings suggest that strong governance structures and transparent ESG practices contribute to market-based performance and investor confidence. The study provides theoretical contributions to stakeholder theory and practical implications for corporate policy-makers and regulators in emerging markets.